f(x) = (4x + 1)/(x - 2). Find f'(x)

  • Google+ icon
  • LinkedIn icon
  • 688 views

Quotient rule: (vu' - uv')/v^2

u = 4x + 1

u' = 4

v = x - 2

v' = 1

Input into formula:

[(x - 2)(4) - (4x + 1)(1)](x - 2)^2

Simplify:

[4x - 8 -4x - 1]/(x - 2)^2 

= -9/(x - 2)^2

Salah S. A Level Economics tutor, A Level Further Mathematics  tutor,...

About the author

is an online A Level Maths tutor who has applied to tutor with MyTutor studying at Warwick University

Still stuck? Get one-to-one help from a personally interviewed subject specialist.

95% of our customers rate us

Browse tutors

We use cookies to improve your site experience. By continuing to use this website, we'll assume that you're OK with this. Dismiss

mtw:mercury1:status:ok